Personal locator services emerge. - Koshima, H. (IEEE spectrum)
Finding a mentally impaired relative, a lost child, or a criminal in a sprawling metropolitan area would be simple if the person were equipped with a personal locator device. The belief that it should be easy to find anyone, anywhere, at any time with a few pushes of a button has caught on with the advent of the Global Positioning System (GPS). People imagine a miniature device, attached to one's person, that reports ones whereabouts almost instantaneously. Add the highly practical need to find missing persons promptly, and the personal locator system (PLS) industry is born. Systems of this nature, whether based on the GPS or some other technology, are being tested throughout the world. The architecture of a PLS is outlined. Six technologies for PLS are discussed: signal direction, signal times of arrival, GPS, server-assisted GPS, enhanced signal strength, and location fingerprinting. The importance to society of this technology is also discussed